2022
DOI: 10.1186/s42483-022-00137-x
|View full text |Cite
|
Sign up to set email alerts
|

The bZIP transcription factor UvbZIP6 mediates fungal growth, stress response, and false smut formation in Ustilaginoidea virens

Abstract: Rice false smut, caused by Ustilaginoidea virens, is one of the most destructive diseases in major world rice-producing regions. Basic leucine zipper (bZIP) proteins, which belong to an evolutionarily conserved transcription factor family and play critical roles in various biological processes in eukaryotes, have been previously identified in U. virens; however, their functions still need to be further elucidated. Therefore, we aimed to analyze the biological roles of UvbZIP6, a member of the bZIP family in U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Moreover, BLAST searches and homologous comparison revealed that some genes involved in conidial development (UV8b_06435, UV8b_04229, UV8b_04359, UV8b_04568, and UV8b_02287), cell wall integrity (UV8b_03905, UV8b_00692), and mycelial growth (UV8b_05833) were down-regulated (Additional file 2: Table S2). The genes related to the biosynthesis of secondary metabolites, including ustilaginoidin biosynthesis genes, cytochrome P450 genes, and non-ribosomal peptide synthetase genes, were also significantly down-regulated (Li et al 2019a;Liu et al 2022;Qu et al 2022). These data indicate that UvHos2 plays a crucial role in secondary metabolism in U. virens.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, BLAST searches and homologous comparison revealed that some genes involved in conidial development (UV8b_06435, UV8b_04229, UV8b_04359, UV8b_04568, and UV8b_02287), cell wall integrity (UV8b_03905, UV8b_00692), and mycelial growth (UV8b_05833) were down-regulated (Additional file 2: Table S2). The genes related to the biosynthesis of secondary metabolites, including ustilaginoidin biosynthesis genes, cytochrome P450 genes, and non-ribosomal peptide synthetase genes, were also significantly down-regulated (Li et al 2019a;Liu et al 2022;Qu et al 2022). These data indicate that UvHos2 plays a crucial role in secondary metabolism in U. virens.…”
Section: Discussionmentioning
confidence: 73%
“…Inoculation assay was performed as described previously (Qu et al 2022). Briefly, U. virens conidial suspension, together with fragmented mycelia, was diluted to 2 × 10 6 conidia/mL and was then injection-inoculated into rice panicles of the variety Changbai15 at about 7 days before heading.…”
Section: Inoculation Assaymentioning
confidence: 99%
“…To investigate the biological functions of CcPELs in C. camelliae , it is necessary to generate targeted gene deletion mutants of the CcPEL s. The PEG-mediated protoplast transformation system has been widely used for genetic transformation in plant-pathogenic fungi ( 28 30 ). Thus, we attempted to establish a PEG-mediated protoplast transformation system for generating deletion mutants in C. camelliae .…”
Section: Resultsmentioning
confidence: 99%